Temperature-Controlled in-situ Tensile Tests of Polymer Tape with differently shaped Single Particles - Sarah Heupl; Julia Maurer; Johann Kastner (e-Journal of Nondestructive Testing)
In electric vehicles (EVs), a variety of polymers are employed for insulation due to their excellent electrical, thermal, and mechanical properties. However, pollution particles within the polymer matrix can significantly impair these properties, as stresses easily introduce defects around such particles. Advanced techniques like X-ray Computed Tomography (CT), combined with mechanical testing, offer valuable insights into the damage mechanisms of these polymers under various conditions. Depending on the application area, operating temperatures can range from very high to very low, resulting in damage mechanisms that differ from those at room temperature. In this study, the influence of temperature on the damage mechanisms of different single particles in a polymer tape was investigated using in-situ computed tomography. Six polymer tensile test specimens – each containing a single particle – were prepared for tensile testing. CT measurements were performed with the RX Solutions Easytom 160, achieving a voxel size of (3 μm)³. Particles of three different shapes were identified: type (I)-particles with high extension in the x-direction and low extension in the y- and z-directions; type (II)-particles Particles with high extension in the x- and z-directions and low extension in the y-direction; type (III)-particles with high extension in the z-direction and low extension in the x- and y-directions. Inspection temperatures of 22 °C and 70 °C were selected. Each specimen was scanned twice: at 0 % strain and 30 % strain. The findings for each particle type were as follows. For type (I)-particles, detachment from the polymer matrix was observed at 22 °C during tensile testing, while at 70 °C, no detachment occurred. Instead, the particles aligned and elongated in the z-direction. For Type (II)-particles, cracking was observed at 22 °C without detachment, whereas at 70 °C, detachment from the polymer matrix occurred, leading to defects above and below the particle. For Type (III)-particles, no defect formation was observed at either temperature. However, alignment and elongation in the z-direction were noted, similar to the behavior of Type (I)-particles at 70 °C. In summary, mechanical testing of polymer tapes with single particles was conducted at two different temperatures, revealing distinct failure mechanisms dependent on particle shape and temperature. These findings enhance our understanding of the behavior of polymers under different conditions, offering valuable insights for damage mechanisms in insulation materials.